Dual demise following laser surgery for twin‐twin transfusion syndrome: Analysis of 52 cases at a single fetal surgery center. (23rd October 2021) - Youssefzadeh, Ariane C.; Glassen, Gabrielle L.; Chon, Andrew H.; Korst, Lisa M.; Esakoff, Tania F.; Afshar, Yalda; Gheorghe, Ciprian P.; Llanes, Arlyn; Chmait, Ramen H.
Abstract: Objective: To evaluate all individual cases of dual twin demise following laser surgery for twin‐twin transfusion syndrome (TTTS). Method: This is an analysis of all monochorionic diamniotic twin gestations with TTTS complicated by dual demise following laser surgery from 2006 to 2019. Cases were reviewed by (1) a fetal surgeon researcher and (2) a panel of independent experienced maternal‐fetal medicine specialists to code an etiology of demise for the donor and recipient, and to assess for possible preventability. Results: Of 753 twins that underwent laser surgery for TTTS, 52 (6.9%) had postoperative dual demise. In this subgroup, gestational age at surgery was 19.5 (16.1–24.9) weeks, and 36 (69.2%) patients were Quintero stage III and IV. The most common etiology was the spectrum of disorders leading to preterm delivery, which included cervical insufficiency, preterm premature rupture of membranes, and preterm labor (44.2% and 48.1%, donor and recipient, respectively). Some degree of preventability was estimated for 23.1% of dual demises. Conclusions: The most common cause of dual demise post laser surgery for TTTS was preterm birth, reinforcing the need for studies regarding the etiology and prevention of post‐fetoscopy prematurity. Nearly one‐quarter of dual demise cases were deemed potentially preventable. Key points: What's already known about this topic? Dual twin demise is an uncommon outcome following laser surgery for twin‐twin transfusion syndrome (TTTS), and limited data have been reported regarding these patients. What does this study add? Through the use of an expert panel, this study reviews both the causes and potential preventability of dual demise following laser surgery for TTTS.